2014
DOI: 10.1007/s13402-014-0213-5
|View full text |Cite
|
Sign up to set email alerts
|

Synergy of leptin/STAT3 with HER2 receptor induces tamoxifen resistance in breast cancer cells through regulation of apoptosis-related genes

Abstract: Our study provides novel evidence indicating that synergy between the leptin/Ob-Rb/STAT3 signalling pathway and the HER2 receptor protects tamoxifen-treated HER2 over-expressing cells from the inhibitory effect of tamoxifen through differential regulation of apoptosis-related genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…Leptin treatment reduced this resistance and this effect was associated with decreased STAT3 regulation of apoptosis-related genes [108]. In ER-negative breast cancer cells, there may be an alternate pathway for mediating the effects of leptin not only via the ObR -STAT3 pathway, but also by induction of the oncogene SK1-ERK1/2-mediated pathway [109].…”
Section: The Role Of Leptin In the Tumour Microenvironmentmentioning
confidence: 99%
“…Leptin treatment reduced this resistance and this effect was associated with decreased STAT3 regulation of apoptosis-related genes [108]. In ER-negative breast cancer cells, there may be an alternate pathway for mediating the effects of leptin not only via the ObR -STAT3 pathway, but also by induction of the oncogene SK1-ERK1/2-mediated pathway [109].…”
Section: The Role Of Leptin In the Tumour Microenvironmentmentioning
confidence: 99%
“…In this study, normal human breast epithelium (184.a1 line) and normal mouse mammary epithelial cells (NMuMG) were used. Furthermore, studies found reduced sensitivity to antiestrogen tamoxifen after the administration of leptin to breast cancer cells (MDA-MB-231, MCF-7, and MCF-7/HER2 cell-lines), especially HER2-overexpressing cells [138], [140].…”
Section: Breast Cancer and Her2 In Obesity: In Vitro And In Vivo Obsementioning
confidence: 99%
“…The obesity-related adipokine leptin has been well characterized as a growth factor for breast cancer and has been recently proposed to decrease sensitivity to tamoxifen in vitro. It has been demonstrated that leptin treatment interferes with the antagonistic effects of tamoxifen in ERα-positive breast cancer cells [32,33] and the synergy between the leptin/Ob-R/STAT3 signaling pathway with the HER2 receptor induces tamoxifen resistance in breast cancer cells through differential regulation of apoptosis-related genes [35]. Interestingly, ObR knockdown significantly enhanced the inhibitory effects of tamoxifen on the proliferation and survival of tamoxifen-resistant cells [34].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, leptin is able to shape the tumor microenvironment by inducing multiple concurrent events, for example, a promotion of angiogenesis and a sustained recruitment of monocytes and macrophages, which in turn secrete VEGF (vascular endothelial growth factor) and proinflammatory cytokines [29][30][31]. However, only a few studies have indicated a role of this adipokine in endocrine resistance, such as tamoxifen resistance [26,[32][33][34][35][36][37], and so far, its involvement in AI therapy resistance has not yet been investigated. Here, we present data showing the involvement of the leptin-mediated signaling pathway in the development of AI therapy resistance, thereby suggesting how blocking leptin signaling could be further exploited for clinical utility in breast cancer resistant settings, especially for obese patients.…”
Section: Introductionmentioning
confidence: 99%